КОМП’ЮТЕРНЕ ТА ФІЗИЧНЕ МОДЕЛЮВАННЯ БЕЗДРОТОВОГО ЗАРЯДНОГО ПРИСТРОЮ ЄМНІСНОГО ТИПУ ДЛЯ МАЛОГАБАРИТНОГО ЕЛЕКТРОТРАНСПОРТНОГО ЗАСОБУ - Павлов, В.Б.; Подольцев, О.Д.; Павленко, В.Є. (Інститут електродинаміки НАН України, Київ, 2024)
The work considers one of the possible approaches to the creation of a capacitive type wireless charger, which allows for non-contact charging of batteries of small-sized vehicles: electric carts, electric scooters, electric scooters. The basis of the development of such a device is the operation of the hybrid DC-DC converter circuit, which operates at a high frequency (550 kHz), transfers energy to the charging circuit using two capacitive elements and allows receiving a constant regulated voltage on the load, which can be either lower or and more input DC voltage. A prototype of such a device has been developed and the results of its experimental research are given, which confirm the possibility of using this scheme for wireless charging of the battery. A Simulink computer model of such a device has been developed, which takes into account the real values ​​of all parameters of the developed prototype and uses the basic model of a lithium-ion battery. According to the results of the calculations, it was determined that for the developed device of the capacitive type, and the largest losses occur in the inductor coils, the value of efficiency, which characterizes the efficiency of the process of transferring electrical energy from the primary power source to the battery, at the initial stage of its charging (when the parameter of the state of the battery SOC =50%) is 80%. References 10, figures 5.